An experimental study of Ge diffusion through Ge2Sb2Te5. (December 2022) - Luong, Minh Anh; Ran, Sijia; Bernard, Mathieu; Claverie, Alain
Abstract: Ge thermal diffusion is not only the phenomenon limiting the decomposition and crystallization of Ge-rich GeSbTe alloys but is also responsible for some of the failures of the phase change memory devices using them. However, Ge diffusion in the canonical Ge2 Sb2 Te5 (GST-225) or in Ge-rich GeSbTe (GGST) alloys has been little studied experimentally. For these reasons, we have designed and set up a series of experiments aimed at highlighting and studying this diffusion within the solid phase, under technologically relevant conditions. For that, dedicated GST/Ge/GST structures have been grown at purpose, and the redistribution of Ge in GST-225 layers during isothermal and isochronal annealing has been studied using scanning and transmission electron microscopy based techniques. While Ge diffusion in amorphous GST-225 is negligible at low temperatures (i.e., below 140 °C), it is fast in crystalline GST-225 above 220 °C and proceeds via the grain boundaries. During such annealing, Ge diffusion is only limited by the emission of Ge atoms from the solid source and by the density of the grain boundaries providing diffusion paths to Ge through the polycrystalline layer, which tends to decrease as a function of the annealing time as the GST grains coalesce. These results show that diffusion phenomena can be activated at moderate temperatures in GST alloys and can change the chemical composition and morphology of Ge/GST composite materials. This supports the hypothesis that Ge diffusion may be responsible for the observed resistance drift and loss of integrity of the Phase Change Memories based on Ge-rich GeSbTe alloys in the SET state.